Utilizing AI Chatbots to Enhance Students' Critical Thinking and Problem-Solving Skills in Numerical Methods to Promote Reproducibility (Sebha University Conference Proceedings, 2024)
Practically every scientific field is impacted by the reproducibility dilemma. It has long been known that a significant amount of the science being generated cannot be reproducible and that findings from science that are not reproducible are at best doubtful and at least effectively insignificant. The principles of creative thinking are presented in this study article, which also emphasizes the need for computational thinking for problem-solving and enhancing mathematical proficiency. It emphasizes how mathematization helps develop problem-solving skills through numerical methods and goes into additional information about the process. In addition, the article addresses teaching with an artificial intelligent AI Chatbot, to achieve reproducibility. The AI Chatbot fosters students' creativity and curiosity while assisting them in comprehending and applying mathematics to practical situations. The study offers scientific insights into how AI technology might enhance student learning and foster mathematical thinking in mathematical classrooms. The current work presents ChatGPT, a conversational paradigm that can execute code on demand in response to computational problems. As part of the interaction, ChatGPT converts each query into the appropriate code, executes the code, and publishes the computed result. Among ChatGPT's noteworthy attributes is its well-known precision in solving numerical problems; as a subject, it does well in calculus, physics, linear algebra, and other courses. We combine this approach with interpretations in MATLAB, and PYTHON. Additionally, a user interface secure environment is needed for the code to run and reproduce the solutions to the mathematical problems presented by this scientific research.